Government at Risk : Contingent Liabilities and Fiscal Risk - Polackova Brixi, Hana (Washington, DC: World Bank and Oxford University Press, 2013)
Conventional fiscal analysis fails to address contingent fiscal risk. The government budget process and documentation generally fail to scrutinize the substantial claims on public resources that are associated with government contingent liabilities, realized and potential. This report fills gaps on our understanding of fiscal risks and develops suitable frameworks for managing them. It offers new analytical concepts, presents country case studies, and based on country case studies, provides a menu of practical ideas for policymakers and scholars to bring fiscal risk within the ambit of public finance. The book is divided into two parts: Part I of this book gives an overview of different approaches to dealing with government fiscal risks. The country examples in this part offer additional conceptual approaches and illustrate some of the discussion in the earlier chapters. Part II presents analytical and institutional approaches that governments might consider when facing risks in specific government programs or sectors. The book indicates that countries differ greatly in their treatment of contingent liabilities and other fiscal risks. In this respect, the book illustrates that contemporary practices have yet to be standardized.